2013
DOI: 10.1103/physrevlett.110.015703
|View full text |Cite
|
Sign up to set email alerts
|

Critical Droplet Theory Explains the Glass Formability of Aqueous Solutions

Abstract: When pure water is cooled at $10 6 K=s, it forms an amorphous solid (glass) instead of the more familiar crystalline phase. The presence of solutes can reduce this required (or ''critical'') cooling rate by orders of magnitude. Here, we present critical cooling rates for a variety of solutes as a function of concentration and a theoretical framework for understanding these rates. For all solutes tested, the critical cooling rate is an exponential function of concentration. The exponential's characteristic conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…However, cryogenic cooling itself can damage the crystal and compromise diffraction quality, often due to ice formation (Haas and Rossmann, 1970; Juers and Matthews, 2001; Juers and Matthews, 2004; Kriminski et al, 2002; Low et al, 1966). Cooling-induced damage is typically reduced by cooling faster and/or adding cryoprotective agents such that the system cools through the freezing point of water to the glass transition before ice can form (Chinte et al, 2005; Shah et al, 2011; Warkentin et al, 2013). The use of pressure to prevent the formation of ice I during cooling has also been successfully applied to several systems (Burkhardt et al, 2012; Kim et al, 2005; Thomanek et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cryogenic cooling itself can damage the crystal and compromise diffraction quality, often due to ice formation (Haas and Rossmann, 1970; Juers and Matthews, 2001; Juers and Matthews, 2004; Kriminski et al, 2002; Low et al, 1966). Cooling-induced damage is typically reduced by cooling faster and/or adding cryoprotective agents such that the system cools through the freezing point of water to the glass transition before ice can form (Chinte et al, 2005; Shah et al, 2011; Warkentin et al, 2013). The use of pressure to prevent the formation of ice I during cooling has also been successfully applied to several systems (Burkhardt et al, 2012; Kim et al, 2005; Thomanek et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments showed that both methanol and ethanol require lower concentrations (w/v) than traditional cryoprotective agents (e.g. glycerol and ethylene glycol) to prevent ice formation in small volumes of plunge-cooled solution (Warkentin et al, 2013). Despite their effectiveness, volatile alcohols have seen little use for cryoprotection in macromolecular crystallography, due in part to the difficulty of working with their high vapor pressures.…”
Section: Introductionmentioning
confidence: 99%
“…There is a claim by [9] that concentrated aqueous solutions, including those of sodium chloride, have been amorphized by cooling rates as low as 60 K s −1 . However, amorphization was not determined by diffraction, but by visual inspection of the transparency of the cooled droplet, by the method described in [10].…”
Section: Amorphizing Solutionsmentioning
confidence: 99%
“…15,16 Furthermore, positions close to the bottom of the channel (10 μm or less) result in cooling rates of the order of 10 5 to 10 6°C s −1 , corresponding to the critical cooling rate for pure water. 17,18 Therefore, under ideal conditions, the ultra-rapid microfluidic cooling technique presented here has the potential to greatly reduce or eliminate the need for cryoprotectants. Interestingly, at the same distance from the heater, a channel four times taller (h = 60 μm) results in a rate Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…Yet, these rates should still be high enough to allow for vitrification at low cryoprotectant concentrations. 18,19 In a first proof-of-principle we used budding yeast as a model system. Yeast cells were grown and resuspended in PM medium containing 800 mM sorbitol as described in the ESI.…”
Section: View Article Onlinementioning
confidence: 99%